Diagnosis dan Tata Laksana Tuberkuloma Serebral: Tinjauan Pustaka - Putri, Lulu Anandita (PT Kalbe Farma Tbk., 2025)
Cerebral tuberculoma is a rare but serious manifestation of tuberculosis (TB) caused by Mycobacterium tuberculosis infection in the central nervous system. This granulomatous lesion, characterized by necrotic tissue in the brain parenchyma, accounts for approximately 1.4% of all TB cases. It predominantly affects high-risk populations including children, HIV/AIDS patients, and immunocompromised individuals. Clinical diagnosis remains challenging due to nonspecific symptoms such as persistent headaches, seizures, and focal neurological deficits that often mimic brain tumors. Advanced neuroimaging, particularly MRI, plays a crucial diagnostic role by demonstrating pathognomonic ring-enhancing lesions with surrounding edema. Cerebrospinal fluid analysis typically reveals lymphocytic pleocytosis, though its sensitivity is limited. Current treatment protocols recommend prolonged (minimum 12 months) combination anti-tuberculosis therapy using isoniazid and rifampin as firstline agents. Adjuvant corticosteroids are indicated for managing paradoxical reactions and cerebral edema. Neurosurgical intervention becomes necessary for large lesions (>2 cm) causing mass effect or hydrocephalus. With timely diagnosis and appropriate treatment, the prognosis is favorable, achieving up to 85% cure rates. However, delayed intervention significantly worsens outcomes, emphasizing the importance of early recognition in endemic regions. This condition highlights the neurological burden of TB and the need for improved diagnostic strategies.